Aggregate effects of a universal social insurance fiscal reform - Arturo Antón; Julio Leal (Inter-American Development Bank (IDB), 2013)
This paper analyzes the aggregate effects of a revenue neutral fiscal-cumsocial policy reform in a typical developing country that consists of two main changes: (1) the implementation of universal social insurance to replace the current dual social protection system (i.e., a reconfiguration of transfers); and (2) the elimination of the current social security payroll tax to replace it with a generalized VAT (i.e., a reconfiguration of taxes). The authors find that this reform increases productivity by 2 percent and output by 3 percent as it improves the allocation of resources across firms and sectors, and generates a substantial change in occupational choices that favors wage earners. As a result, wages (before transfers) increase for all employees. Also, due to the reconfiguration of transfers, earnings (wages after transfers) for informal employees increase relative to the earnings of formal employees, which decreases inequality. However, we also find that the reform could affect some groups in the population, given the regressive nature of VAT and heterogeneity in the valuation of transfers across workers.
hdl:11319/4580
Keywords: E62; H550; O170; O470; 330; Total factor productivity; Fiscal policy; Social security; Informal labor markets